Perancangan Aplikasi Sistem Informasi Manajemen Kehadiran Karyawan Menggunakan Metode UML (Studi Kasus di UNDIRA) - Giri Purnama; Imron Rizki Maulana (Universitas Sains Indonesia Publishing, 2025)
Employee attendance management is a crucial aspect of human resource administration. UNDIRA faces challenges in attendance recording, such as limitations in reporting flexibility, data integration, and attendance recapitulation. This study aims to develop an Employee Attendance Management Information System application using the UML method. This research applies UML modeling, including Use Case Diagram, Class Diagram, Sequence Diagram, and Activity Diagram, to design a more structured and efficient system. The developed system enables real-time attendance management, report generation based on date, user level, and specific time ranges, while also enhancing transparency and accuracy in record-keeping. Furthermore, the system is integrated with fingerprint biometric technology, ensuring attendance data security and minimizing potential fraud. The study's findings indicate that the system meets the administrative attendance needs at UNDIRA, providing features that enhance reporting efficiency and data management. The implementation of this system can serve as a reference for other institutions facing similar challenges in employee attendance management. In the future, this research can be further developed by integrating the system into Human Resource Management (HRM) platforms and applying artificial intelligence technology for predictive attendance analysis.